MENINGKATKAN KOMITMEN DAN KEMAMPUAN PARA PENDIDIK SMPN 18 MEDAN MENYUSUN RPP INOVATIF MELALUI KERJA PRAKTEK DENGAN TEKNIK UMPAN BALIK - Bambnag Sudewo (Jurnal Sabilarrasyad, 2020)
The new RPP model to meet the demands of Minister of National Education Regulation number 22 in 2016, hereinafter referred to as Innovative RPP, is new for educators. Educators are required to implement learning that changes the educational paradigm, namely from the teaching paradigm to the learning paradigm. An obstacle for educators, because they have to leave learning strategies that are centered on educators (teacher center oriented) to student centered learning strategies (student center oriented). The benefits of this research, especially for educators who are the subject of research, are the increased commitment and ability of educators. So that it can make Innovative RPP to meet the demands of Minister of National Education Regulation number 22 in 2016 and facilitate educators in facing certification. The benefit in enriching the patterns of educating educators is the Pattern of Practical Work that is effective and efficient. This research method is Action Research with Stephen Kemmis model. Job Training Strategies with Feedback Techniques, designed in 3 (three) cycles. Research results: 1). An increase in the commitment of educators to prepare innovative lesson plans, which is as much as 95% of educators are able to achieve a value of 4.00-5.00 on a scale of 1-5, and 2). An increase in the ability of educators to compile Innovative RPPs, as many as 95% of educators are able to reach grades 4.00-5.00 on a scale of 1-5. The conclusion of this study, that the Job Training Strategies with Feedback Techniques can improve the commitment and ability of 18 Medan Middle School educators to compile Innovative RPPs.